KUALITAS PELAYANAN PASANG BARU LISTRIK PRABAYAR PADA PT. PLN (PERSERO) RAYON DARMO PERMAI SURABAYA - Bariroh, Umu; Yuliyanti, Tri (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Quality of New Possible Service Proportar at PT. PLN (Persero) Rayon Darmo Permai Surabaya. One of the main tasks of the government is to provide services, including in terms of electrical services. PLN is the only BUMN appointed as a provider of electric power to meet the electricity needs of the people of Indonesia. So this study aims to determine and value the quality of public services at PT. PLN (Persero) area Darmo Permai Surabaya necessary of electric power can be seen from the increasing demand for electricity supply in each region. This becomes the trigger of PT. PLN (Persero) to make innovations in the form of products to help meet the electricity needs of consumers. PLN continues to improve its service productivity with Prepaid Electricity. The method used in this research is qualitative research method with descriptive type. The data were collected by interview, questioner and observation. Data analysis techniques conducted in this study is data reduction by selecting data according to research, also presenting data by presenting data that has been reduced and obtained from PT. PLN (Persero) Darmo Permai area of Surabaya, and also using data analysis techniques draw conclusions by deducing data that has been reduced and presented. Based on the results of research can be concluded that the quality of electricity service prepaid in PT. PLN (Persero) Darmo Permai Surabaya area can be said is good enough. But on the other hand, there needs to be improvements made. Lack of adequate parking facilities, but also the number of booths available, indirectly this will affect the quality of service itself. Â  Keywords: Quality of service, public service, electricity prepaid